Effect Size of General English Modules Development through MPI + R Model on the Lecturer Professionalism - Roslina; Hanna; Lio, Asrun; Nasrul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Previous studies on General English (GE) showed that the challenge to lecturer professionalism is the issue of providing teaching materials. While Instructional Design provided pedagogic activities, so the General English Modul development through Model Pengembangan Instruksional (MPI) + Revalidation (R) was propose to be an alternative solution. For that reason, a case study with an experimental design done to measure the effect size of MPI + R on the lecturers professionalism development. Under one goup pre and post test design, three GE Lecturers at Universitas Sembilanbelas November Kolaka (USN Kolaka) involved in GE module development through ID model MPI + R . The development phase done during September 2022 to Mey 2023. The data collected by using Danielson Teaching Framework Instrument and the effect size calculated by nonparametric and Cohen-D test. The effect size calculation showed that the ID model MPI + R has a great effect on the lecturer professionalism. It can be concluded that MPI + R is able to be an alternative solution for lecturer professionalism development.